Analyzing the influence of excessive digital technologies usage towards emotional intelligence development of undergraduate IPTA students in Klang Valley, Selangor - Amin, Samir Muhazzab; Mohd Nizam, Khairunnisa; Nazuri, Nur Shuhamin; Ahmad Suhaimi, Siti Shazwani (RSIS International, 2024)
The relationship between social media usage, online gaming usage, online shopping usage, social skills and emotional self-regulation has been studied in many Western countries. Nevertheless, the relationship between these variables has not been extensively studied. The objective of this study is to determine the influence of social media usage, online gaming usage, online shopping usage on undergraduate students’ social skills and emotional self-regulation. A total of 400 undergraduate students from eight universities in Malaysia participated in this study. In terms of social media usage, the levels are high, while online gaming and online shopping usage are moderate. On the other hand, respondents exhibit very low emotional self-regulation, whereas their social skills are notably high. There are differences between males and females in terms of social skills and emotional self-regulation. Females exhibit higher levels of social skills, while males show higher levels of emotional self-regulation. Through the survey, the study confirmed that all variables have a significant relationship towards social skills and emotional self-regulation. The study also found that social media usage has the most significant positive impact on social skills. Meanwhile, the relationship between social media usage has negatively significant towards emotional self-regulation. It can be concluded that the relationships between social media usage, online gaming usage, online shopping usage, social skills, and emotional self-regulation among undergraduate students in Malaysia have significant implications.